Experimental analysis to determine the relationship between noise and back pressure for muffler design – Part II: Experimental results - Mohiuddin, A. K. M. (IIUM Press, 2011)
This chapter describes the final part of the detailed methodology of relationship between noise and back pressure for muffler design. This part includes experimental setup, experimental procedures, results and discussions. The experimental data show a general shape of an average design ofthe muffler which would be the most suitable for the test car.